Disability and health‐related quality of life in Chinese patients with rheumatoid arthritis: A cross‐sectional study. (21st October 2018) - Zhou, Yunshan; Wang, Xiuru; An, Yuan; Zhang, Xiaoying; Han, Shuling; Li, Xiaofeng; Wang, Lizhi; Wang, Caihong; Wang, Yongfu; Yang, Rong; Wang, Guochun; Lu, Xin; et al.
Abstract: Aim: The objective of this study was to evaluate the impact of rheumatoid arthritis (RA) on physical function and health‐related quality of life (HRQoL) in China. Method: A cross‐section survey was conducted in 21 general hospitals in China. Eight hundred and seven patients were recruited. Data on demographics, clinical data, physical function (Stanford Health Assessment Questionnaire Disability Index, HAQ‐DI) and HRQoL (Study Short Form 36 Health Survey, SF‐36) were collected on site. Results: In our cohort, physical function was impaired in 77.6% of patients (HAQ‐DI >0). The median (interquartile range, IQR) of HAQ‐DI was 0.750 (0.125, 1.500). Rated by HAQ‐DI 0‐1, >1‐2, and >2‐3, percentage of patients with mild, moderate and severe disability was 61.0%, 25.4%, and 13.6%, respectively. Older age, long disease duration, presence of extra‐articular manifestations, tender joint count (TJC), overall status (assessed by patient Global Visual Analogue Scale [G‐VAS] and physician G‐VAS) and lacking disease‐modifying anti‐rheumatic drugs were identified as predictive factors for worse physical function ( P  <   .05). The composite scores of SF‐36 in the observed patients were: physical component summary 40.4 (IQR 27.4, 60.3), and mental component summary 49.0 (IQR 33.6, 70.9). Impaired physical health may be predicted by low income, presence of extra‐articular manifestations, TJC, patient G‐VAS and high HAQ‐DI. Predictors for suboptimal mental health were low income, physical labor, married status, increased swollen joint count (SJC), physician G‐VAS and high HAQ‐DI. Conclusion: Rheumatoid arthritis has profound effects on physical function and HRQoL in Chinese patients. Patients with identified predictive factors for poor outcome should be closely monitored.